Parseval’s Identity for Low-Dimensional Nilpotent Lie Groups G5,1, G5,2, G5,3 and G5,5 - Bhatta, CR (Kathmandu University Journal of Science, Engineering and Technology, 2010)
We prove the Parseval's identity for low-dimensional nilpotent Lie groups such as G5,1, G5,2, G5,3 and G5,5 respectively which are important for proving Hardy uncertainty principles type result. Keywords: Fourier transform; Hilbert schmidt norm; Kernel function. DOI: 10.3126/kuset.v5i1.2844 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 23-30